Successive Site Translocating Inoculation Improved T Cell Responses Elicited by a DNA Vaccine Encoding SARS-CoV-2 S Protein - Tian, Xiangxiang; Zhang, Yifan; He, Zhangyufan; Li, Shaoshuai; Yan, Dongmei; Zhu, Zhaoqin; Wan, Yanmin; Wang, Wanhai (Frontiers in Immunology, 2022)
A variety of methods have been explored to increase delivery efficiencies for DNA vaccine. However, the immunogenicity of DNA vaccines has not been satisfactorily improved. Unlike most of the previous attempts, we provided evidence suggesting that changing the injection site successively (successively site-translocated inoculation, SSTI) could significantly enhance the immunogenicity of DNA vaccines in a previous study. To simplify the strategy and to evaluate its impact on candidate SARS-CoV-2 vaccines, we immunized mice with either a SARS-CoV-2 spike-based DNA vaccine or a spike protein subunit vaccine via three different inoculation strategies. Our data demonstrated that S protein specific antibody responses elicited by the DNA vaccine or the protein subunit vaccine showed no significant difference among different inoculation strategies. Of interest, compared with the conventional site fixed inoculation (SFI), both successive site-translocating inoculation (SSTI) and the simplified translocating inoculation (STI) strategy improved specific T cell responses elicited by the DNA vaccine. More specifically, the SSTI strategy significantly improved both the monofunctional (IFN-γ+IL-2-TNF-α-CD8+) and the multifunctional (IFN-γ+IL-2-TNF-α+CD8+, IFN-γ+IL-2-TNF-α+CD4+, IFN-γ+IL-2+TNF-α+CD4+) T cell responses, while the simplified translocating inoculation (STI) strategy significantly improved the multifunctional CD8+ (IFN-γ+IL-2-TNF-α+CD8+, IFN-γ+IL-2+TNF-α+CD8+) and CD4+ (IFN-γ+IL-2-TNF-α+CD4+, IFN-γ+IL-2+TNF-α+CD4+) T cell responses. The current study confirmed that changing the site of intra muscular injection can significantly improve the immunogenicity of DNA vaccines.